On the Growth Effect of Stock Market Liberalizations - Gupta, Nandini; Yuan, Kathy (Review of Financial Studies, 2009)
[We investigate the effect of a stock market liberalization on industry growth in emerging markets. Consistent with the view that liberalization reduces financing constraints, we find that industries that are more externally dependent and face better growth opportunities grew faster following liberalization. However, this growth increase appears to come from an expansion in the size of existing firms rather than through the entry of financially constrained new firms. We show that following liberalization, new firm growth occurs in countries and industries with lower entry barriers. Hence, liberalization has a more uniform growth impact if accompanied by competition-enhancing reforms.]